Upper extremity compartment syndrome in a hemophilic infant - Giuseppe Stranieri; Antonio Pergola; Pasqualina Stranieri (Journal of Pediatric Surgery Case Reports, 2022)
Acute compartment syndrome is an important differential diagnosis to consider given the correct predisposing history and clinical presentation. However, spontaneous compartment syndrome in childhood is a rare occurrence. This case illustrates acute compartment syndrome in 32-month-old child admitted to pediatric oncohematology for hemophilia (factor VIII° not detectable).